PENGELOLAAN WAKTU BELAJAR DALAM PERSPEKTIF AL-QUR,AN DAN HADITS - Adawiyah, Roviatul; Fauji, Imam (As-Sulthan Journal of Education, 2024)
This research utilizes the literature research method and looks at the main Islamic sources relating to the concept of time and its management. The results show that the Qur'an and Hadith emphasize the importance of time as a gift that should be well utilized for learning and forming discipline and Islamic character in students. It is evident that the application of Islamic values in learning time management improves students' efficiency, discipline and learning outcomes. This method also helps build Islamic character, which includes discipline, responsibility and respect for time. But there are problems such as students who do not know and teachers who cannot apply these principles thoroughly. To improve the quality of learning and students' morals, this study suggests strengthening Qur'anic and Hadith-based educational methods.